Vacancy and curvature effects on the phonon properties of single wall carbon nanotube. (5th January 2018) - Howlader, Ashraful Hossain; Islam, Md. Sherajul; Tanaka, Satoru; Makino, Takayuki; Hashimoto, Akihiro
Abstract: Single wall carbon nanotube (SWCNT) is considered as an ideal candidate for next-generation nanoelectronics owing to its unusual properties. Here we have performed an in-depth theoretical analysis of the effect of vacancy defects and curvature on the phonon properties of and SWCNTs using the forced vibrational method. We report that Raman active E2g mode softens towards the low-frequency region with increasing vacancies and curvature in both types of CNTs. Vacancy induces some new peaks at low-frequency region of the phonon density of states. Phonon localization properties are also manifested. Our calculated mode pattern and localization length show that optical phonon at Raman D-band frequency is strongly localized in vacancy defected and large curved CNTs. Our findings will be helpful in explaining the thermal conductivity, specific heat capacity, and Raman spectra in vacancy type disordered CNTs, as well as electron transport properties of CNT-based nanoelectronic devices.